Born with a copper spoon : a global history of copper, 1830-1980 - Declercq, Robrecht, 1987-; Frøland, Hans Otto, 1958-; Money, Duncan, 1988- (Vancouver ; Toronto : UBC Press, 2022)
"Born with a Copper Spoon examines how the metal has been produced, distributed, controlled, and sold around the globe. Over the past two centuries, industrial societies hungry for the highly conductive, corrosion-resistant metal--essential for light, power, and communication--have demanded ever-increasing quantities of copper. From copper cartels and the futures market to the consequences of resource nationalism, Born with a Copper Spoon has a global scope. However, this is not simply a narrative of ever-increasing and deepening global connections, as global history often is. It is also about periods of deglobalization, fragmentation, and attempts to sever connections, as was the case in the mid-twentieth century, when a bitter contest over ownership of mineral resources briefly threatened to cause a major realignment of the world economy. Throughout history, copper production has spawned its own practices, technologies, and a constantly changing political economy. Large-scale production has affected ecologies, states, and companies, while creating and even destroying local communities dependent on volatile commodity markets. The first president of Zambia, Kenneth Kaunda, once remarked that Zambians were "born with a copper spoon in our mouths," but few societies managed to profit from copper's abundance. Contributors to this far-reaching collection cover the finance, technology, labour, business, politics, and environmental impact of what is one of the world's most important metals."--
The Gains of Going Global: The Return on Investment in International Copper Mining during the Second Industrial Revolution / Klas Rnb砣k, Oskar Broberg, and Dimitrios Theodoridis -- Futures Markets as Trustbusters: The Secran Copper Cartel and the London Metal Exchange, 1887-89 / Nathan Delaney -- American Mining Engineers and the Global Copper Industry, 1880-1945 / Duncan Money -- The Path to Dominance: American Copper Mining, 1880-1916 / Jeremy Mouat -- Comparing Copper Nationalism in Zambia and Papua New Guinea, 1964-1974 / Ingeborg Guldal and Frida Brende Jenssen -- Copper Mining in Cuba at the Beginning of Mining Internationalization, 1829-70 / gel Pascual Martez-Soto, Miguel Pez de Perceval, and Susana Martez-Rodruez -- Copper Communities on the Central African Copperbelt, 1950-2000 / Iva Pe財 -- Confronting Kennecott: The Lost City of Bingham Canyon and the History of Mining-Induced Resettlement / Brian James Leech -- Global and Local Interactions: The Great War, Global Trade, and Community Impacts in the Australian Copper Mining Industry, 1900-20 / Erik Eklund -- The Copper Industry as National Enterprise in Modern Japan / Patricia Sippel -- Katanga and the American World of Copper: Mechanization, Vertical Integration, and the Territorialization of Colonial Capitalism, 1900-30 / Robrecht Declercq -- The Establishment of Iran's Copper Mining Industry: The Downfall of Anaconda and Selection Trust in the 1960s-70s / Abdolreza Alamdar and Ali A. Saeidi -- Copper in Chile: From the New Deal to Full Concessions, 1955-81 / Angel Soto and Alejandro San Francisco -- Producer Cartel, International Commodity Agreement, and the Role of the US Government Copper Stockpile / Hans Otto Fr
Includes bibliographical references and index.
Keywords: 1800-1999.; Copper industry and trade -- History -- 19th century; Copper industry and trade -- History -- 20th century; Copper industry and trade; Copper mines and mining -- History -- 19th century; Copper mines and mining -- History -- 20th century; Copper mines and mining; History